Potencial evocado auditivo por frequência específica em neonatos: utilização de diferentes estímulos - Quinto, Stella Medianeira Soares (2018)
Different acoustic stimuli can be used to capture the Auditory Brainstem Response. Thus, this study aimed to analyze and compare the results of the absolute latency and amplitude of the V wave of Auditory Brainstem Response in newborns, using tone burst and iChirp stimuli at specific frequencies, at different intensities of presentation. To compare the recording time of this potential with the different stimuli studied. In addition to providing reference values of absolute latency and amplitude of the V wave in relation to the stimulus iChirp specific frequency. The study sample consisted of 32 full-term newborns, 14 of whom were male and 18 were female. The protocol for recording auditory brainstem evoked potentials with tone burst and iChirp stimuli was applied, at intensities of 60, 40 and 20 dBnHL and frequencies of 500, 1000, 2000 and 4000 Hz. Data were analyzed by means of statistical tests. It was observed that the values for the V wave latency of the Auditory Brainstem Response with iChirp stimulus were significantly higher when compared to the tone burst stimulus, in the frequencies of 500 and 2000Hz. Regarding the amplitude of the V wave, significantly higher responses were evoked in most of the frequencies and intensities investigated with the iChirp stimulus, proving to be an effective stimulus in low levels of stimulation. In addition, the execution time of the iChirp procedure was significantly lower, which facilitated the performance of the procedure in the sample studied. Reference values for the iChirp specific frequency were presented.